Pengaruh Penerapan Sistem E-Filing, E-Billing, Sosialisasi Pajak Dan Pemahaman Perpajakan Terhadap Kepatuhan Wajib Pajak Orang Pribadi - Fitriani; Baiq Kisnawati; Rusli Amrul (Lembaga Pengembangan, Penelitian dan Pengabdian Kepada Masyarakat (LP3M) Sekolah Tinggi Ilmu Ekonomi AMM (STIE AMM) Mataram, 2025)
The purpose of this study is to ascertain how individual taxpayer compliance at the Tax Office (KPP) pratama of Bima Regency is affected by the adoption of the e-filing system, e-billing, tax socialization, and tax understanding. This is a quantitative associative study. With a sample of 100 taxpayers, the population in this study consists of individual taxpayers who are registered at KPP Bima Regency. One hundred questionnaires were distributed in order to gather data; all of them were returned and found to be valid. SPSS 24 was used to analyze the data using multiple linear regression analysis and traditional assumption tests. According to the study's findings, taxpayer compliance is significantly impacted by the use of e-billing and tax knowledge. The introduction of e-filing and tax socialization, on the other hand, have no discernible impact. Additionally, e-filing, e- billing, tax socialization, and tax comprehension all contribute to 65.1% of taxpayer compliance, with other factors outside the scope of the study's regression model accounting for the remaining 34.9%.